The level of fetal attachment in women with the threat of preterm birth in the third trimester of pregnancy and the psychomotor development of the first year of life considering mother-child interaction - Grinko, Natalia (ScienceRise: Medical Science, 2020)
The aim of the research is to study the level of attachment to the fetus of women with the threat of premature birth in the third trimester of pregnancy and psychomotor development of the baby in the first year of life. Materials and methods. The study included 150 pregnant women in the third trimester (23-37 weeks), and their men. Of these, the main group consisted of 120 women with the risk of preterm birth in the last trimester of pregnancy (MG). The comparison group consisted of 30 women with physiological pregnancy (CG). Results and discussion. Women with MG were found to have a maternal fetal attachment level of 71.0±1.0 (attachment disorder) and women with a CG of 51.0±2.0 (sufficient attachment level). Assessment of the psychomotor development of the child during the first year of life showed a tendency to lag its indicators in children of mothers from MG (after the second examination of MTG compared with the infants of women with CG and MGK during all periods of observation (p<0.05). Such a difference in indicators of psychomotor development was observed at the third survey: the level of development of children of mothers of CG was significantly higher than in women with MG. In the fourth survey, children of MTG mothers (29.0) showed better psychomotor development rates than infants of MCT women (27.5), but lower than those of CG (29.4). Subsequently, the level of psychomotor development of children with CG and MTG was almost equal to that of children of MCG (28.1), which were lower than in other groups. When reaching the age of one year, the children of MTG mothers showed the best level of psychomotor development (29.2), almost the same results were observed in children with CG (29.1), and indicators of MCG children were lower (28.5). Conclusions. Among the negative factors that provoke the formation of dyadic interaction disorders, psychological unpreparedness for motherhood and a low level of attachment to the fetus of women with the threat of premature birth during the third trimester of pregnancy are leading